NUTRIENT CONCENTRATIONS IN COASTAL WATERS OF KHANH HOA PROVINCE - Vinh, Le Thi (Vietnam Journal of Marine Science and Technology, 2009)
Results of most studies on distribution of nutrients in Khanh Hoa coastal waters (period of 2000-2007) were collected and considered. The statistics indicated that ranges of nutrient concentrations and molar ratios of N/P and N/Si are as follows: Van Phong - Ben Goi bay, NH3,4 : 0 - 69 µgN/l; NO 2 : 0 - 3.7 µgN/l , NO3 : 30 - 90 µgN/l; PO4 : 1.3 - 21.3 µgP/l; SiO3 : 44 - 968 µgSi/l; N/P: 5.83 - 93.0 and N/Si: 0.15 - 2.7. Nha Phu lagoon - Binh Cang bay, NH3,4: 0 - 51 µgN/l; NO2 : 0 - 6.1 µgN/l , NO3: 53 - 182 µgN/l; PO4: 2.3 - 25.0 µgP/l; SiO3 : 134 - 3155 µgSi/l; N/P: 8.95 - 47.89 and N/Si are always below 1. High concentrations of NO3 are observed in Nha Phu lagoon. Nha Trang bay, NH3,4: 0 - 34µgN/l; NO2: 0 - 2.1µgN/l , NO3 : 38 - 51 µgN/l; PO4: 1.0 - 20.0 µgP/l; SiO3: 187 - 563 µgSi/l; N/P: 5.33 - 39.47 and N/Si are always below 1. However, in Cua Be waters, nutrient concentrations are very much higher (maximum of NH3,4: 432 µgN/l; NO2: 66.6 µgN/l, NO3: 508 µgN/l; PO4: 112.5 µgP/l; N/P: 9.71 - 78.65 and N/Si: 0.07 - 2.63). Thuy Trieu lagoon - Cam Ranh bay, NH3,4: 0 - 296 µgN/l; NO2: 0 - 10.5 µgN/l, NO3 : 28 - 70µgN/l; PO4: 1.0 - 26.8 µgP/l; SiO3: 193 - 3845 µgSi/l; N/P: 5.82 - 166.7 and N/Si are always below 1. Nutrient concentrations in waters almost were not high except for Nha Phu lagoon and Cua Be. N/Si ratios higher than 1 are observed in dry hot period at VanPhong - BenGoi and Cua Be.